Chemistry of superconductor materials : preparation, chemistry, characterization, and theory - Vanderah, Terrell A. (Materials science and process technology series. Electronic materials and process technology., 1992)
Reviews the chemistry of high Tc superconductors. Provides the structural and synthetic solid-state chemistry of oxide superconductors as well as reference material on characterization methods.